Flexural strengthening and rehabilitation of continuous reinforced concrete beams using BFRP sheets: Experimental and analytical techniques - Mu'tasim Abdel-Jaber; Rawand Al-Nsour; Ahmed Ashteyat (Composites Part C: Open Access)
The introduction of Basalt Fiber-Reinforced Polymer (BFRP) materials marks a significant step forward in sustainable construction practices. This study investigates the use of externally bonded low and high-dense BFRP sheets to enhance the flexural strength and durability of reinforced concrete (RC) beams with compressive strengths of 20 and 32 MPa. Analyzing a total of ten two-span RC beams, each with a length of four meters, the study included four beams that were strengthened using low-dense sheets and four beams that were rehabilitated with high-dense sheets after being subjected to 70 % of their ultimate load capacity. Additionally, two beams were used as control samples to compare the effects of the strengthening and rehabilitation techniques. The research demonstrates the effectiveness of BFRP in boosting structural integrity. The findings revealed substantial improvements in flexural strength, with increases ranging from 22.6 % to 80 %, along with enhanced ductility. These results were closely aligned with predictions made using Finite Element Modeling, underscoring the potential of BFRP sheets in advancing the performance and longevity of RC beams. Theoretical outcomes agreed well with experimental findings, in alignment with the ACI 440.2R-08 guidelines.